Anchoring and adjustment in software estimation. - Aranda, Jorge (Software engineering notes.)
Anchoring and adjustment is a form of cognitive bias that affects judgments under uncertainty. If given an initial answer, the respondent seems to use this as an 'anchor', adjusting it to reach a more plausible answer, even if the anchor is obviously incorrect. The adjustment is frequently insufficient and so the final answer is biased. In this paper, we report a study to investigate the effects of this phenomenon on software estimation processes. The results show that anchoring and adjustment does occur in software estimation, and can significantly change the resulting estimates, no matter what estimation technique is used. The results also suggest that, considering the magnitude of this bias, software estimators tend to be too confident of their own estimations.